2008
DOI: 10.1523/jneurosci.1965-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Novel Representations in Primary Motor Cortex and Premotor Neurons during Associative Learning

Abstract: Neurons in the motor areas of cortex play a key role in associating sensory instructions with movements. However, their ability to acquire and maintain representations of novel stimulus features, especially when these features are behaviorally relevant, remains unknown. We investigated neuronal changes in these areas during and after associative learning, by training monkeys on a novel reaching task that required associating target colors with movement directions. Before and after learning, the monkeys perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…There is some evidence that neurons in monkey M1 are sensitive to the location (or other features) of the visual cue (Zhang et al, 1997;Zach et al, 2008;Saleh et al, 2010). However, previous fMRI studies in humans (Toni et al, 1999;Stark and Zohary, 2008;Chouinard and Goodale, 2009), which contained a visual target or a visual cue, did not show any visually induced M1 activation.…”
Section: What Are the Relevant Visual Features In The Display Drivingmentioning
confidence: 95%
See 1 more Smart Citation
“…There is some evidence that neurons in monkey M1 are sensitive to the location (or other features) of the visual cue (Zhang et al, 1997;Zach et al, 2008;Saleh et al, 2010). However, previous fMRI studies in humans (Toni et al, 1999;Stark and Zohary, 2008;Chouinard and Goodale, 2009), which contained a visual target or a visual cue, did not show any visually induced M1 activation.…”
Section: What Are the Relevant Visual Features In The Display Drivingmentioning
confidence: 95%
“…For example, using a visuomotor rotation task, which introduces a constant angular difference between the motor trajectory of the hand and its viewed trajectory on the screen, Alexander and colleagues showed that M1 neurons are sensitive to the target position on the screen (Alexander and Crutcher, 1990;Shen and Alexander, 1997a). Furthermore, the sensitivity of neurons in M1 to sensory stimuli often depends on their functional relevance: when the color of a visual cue carried crucial information to indicate the required hand movement, a considerable fraction of M1 neurons (20%) displayed color sensitivity (Zach et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, modulation of variability might represent adjustments of the forward model that the brain can use to test different movement plans to minimize on-line corrections. Alternatively, the variability may represent the process selecting the association between an instruction (TO) and a new specific action (movement direction) (Wise et al, 1996;Zach et al, 2008). The association requires few (if any) changes in the kinematics to dynamics transformations since there was no alternation in the relationship between movement and muscle activity.…”
Section: Premovement Variability and Motor Statesmentioning
confidence: 99%
“…Psychophysical studies provided evidence for the nature of sensorimotor learning by testing features such as dynamics of acquisition, generalization, and consolidation (Krakauer et al, 1999;Donchin et al, 2003;Caithness et al, 2004). In parallel, physiological studies have demonstrated that neuronal activity in the motor cortex conveys information about the characteristics of the required movement, such as the desired direction (Georgopoulos et al, 1982(Georgopoulos et al, , 1983 and muscle forces (Evarts, 1968), which can change through learning (Mitz et al, 1991;Chen and Wise, 1995;Wise et al, 1996Wise et al, , 1998Gandolfo et al, 2000;Paz et al, 2003;Zach et al, 2008).…”
Section: Introductionmentioning
confidence: 99%